Distribution and localization of phosphatidylinositol 5‐phosphate, 4‐kinase alpha and beta in the brain. Issue 2 (26th June 2020) - Noch, Evan K.; Yim, Isaiah; Milner, Teresa A.; Cantley, Lewis C.
Abstract: Phosphatidylinositol‐4, 5‐bisphosphate (PI‐4, 5‐P2 ) is critical for synaptic vesicle docking and fusion and generation of the second messengers, diacylglycerol and inositol‐1, 4, 5‐trisphosphate. PI‐4, 5‐P2 can be generated by two families of kinases: type 1 phosphatidylinositol‐4‐phosphate 5‐kinases, encoded by PIP5K1A, PIP5K1B and PIP5K1C, and type 2 phosphatidylinositol‐5‐phosphate 4‐kinases, encoded by PIP4K2A, PIP4K2B, and PIP4K2C. While the roles of the type 1 enzymes in brain function have been extensively studied, the roles of the type 2 enzymes are poorly understood. Using selective antibodies validated by genetic deletion of pip4k2a or pip4k2b in mouse brain, we characterized the location of the enzymes, PI5P4Kα and PI5P4Kβ, encoded by these genes. In mice, we demonstrate that PI5P4Kα is expressed in adulthood, whereas PI5P4Kβ is expressed early in development. PI5P4Kα localizes to white matter tracts, especially the corpus callosum, and at a low level in neurons, while PI5P4Kβ is expressed in neuronal populations, especially hippocampus and cortex. Dual labeling studies demonstrate that PI5P4Kα co‐localizes with the oligodendrocyte marker, Olig2, whereas PI5P4Kβ co‐localizes with the neuronal marker, NeuN. Ultrastructural analysis demonstrates that both kinases are contained in axon terminals and dendritic spines adjacent to the synaptic membrane, which support a potential role in synaptic transmission. Immunoperoxidase analysis of macaque and human brain tissue demonstrate a conserved pattern for PI5P4Kα and PI5P4Kβ. These results highlight the diverse cell‐autonomous expression of PI5P4Kα and PI5P4Kβ and support further exploration into their role in synaptic function in the brain. Abstract : Phosphatidylinositol‐4, 5‐bisphosphate (PI‐4, 5‐P2 ) is critical for synaptic vesicle docking and fusion and is generated by either the type 1 phosphatidylinositol‐4‐phosphate 5‐kinases (PI4P5Ks) or the type 2 phosphatidylinositol‐5‐phosphate 4‐kinases (PI5P4Ks). In this study, we describe the neuro‐anatomical localization of PI5P4Kα and PI5P4Kβ in the normal brain. PI5P4Kα is expressed in both oligodendrocytes and some neurons, while PI5P4Kβ is expressed solely in neurons. By electron microscopy, both kinases are located in a peri‐synaptic distribution in axon terminals and dendritic spines, suggesting a role in neuro‐transmission, possibly through synaptic vesicle docking, recycling, and/or fusion.